The Influence Of Physical Work Environment And Work Discipline On Employee Performance: A Study At The Dodol Picnic Garut Production Division - Muhammad Raisa Alawi; Ratna Komala Putri; Didin Kristinawati (Eduvest - Journal of Universal Studies, 2025)
The decline in workforce performance at Dodol Picnic Garut has become a strategic issue that has impacted productivity and work quality. Two main factors believed to contribute to this problem are an unsupportive physical work environment and low employee discipline. Therefore, this study focuses on analyzing and testing the extent to which the physical work environment and work discipline influence employee performance. This study employs a descriptive quantitative approach using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. A total of 110 respondents participated in this study through saturated sampling techniques. Data collection was conducted through interviews, participatory observation, and the distribution of structured questionnaires, which were then analyzed using SmartPLS software. The results of the study indicate that the physical work environment variable has a significant and strong influence on improving employee performance, with a p-value of 0.000 for male respondents and 0.003 for female respondents, and an effect size (f²) of 0.531, reflecting a high influence. Meanwhile, the work discipline variable showed a significant influence only on the male respondent group (p = 0.019), but not on the female group (p = 0.248).